2021
DOI: 10.3390/s21062196
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Nuclear Materials in Urban Environments Using Mobile Sensor Networks

Abstract: Radiation detectors installed at major ports of entry are a key component of the overall strategy to protect countries from nuclear terrorism. While the goal of deploying these systems is to intercept special nuclear material as it enters the country, no detector system is foolproof. Mobile, distributed sensors have been proposed to detect nuclear materials in transit should portal monitors fail to prevent their entry in the first place. In large metropolitan areas, a mobile distributed sensor network could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A network of mobile distributed sensors was deployed on a vehicle platform to detect mobile radioactive sources. It was found that the detection time of mobile radioactive sources was afected by the speed of the source and the number of mobile detectors [18]. Studies [19] demonstrated that the fusion of extensive data generated by radiation detectors employing Pearson's methodology signifcantly enhances the source detection efectiveness of mobile radioactive materials.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A network of mobile distributed sensors was deployed on a vehicle platform to detect mobile radioactive sources. It was found that the detection time of mobile radioactive sources was afected by the speed of the source and the number of mobile detectors [18]. Studies [19] demonstrated that the fusion of extensive data generated by radiation detectors employing Pearson's methodology signifcantly enhances the source detection efectiveness of mobile radioactive materials.…”
Section: Related Workmentioning
confidence: 99%
“…Terefore, μ and σ 2 can be calculated by introducing the measured RSSI values into equations (17) and (18). To compute the Gaussian distribution corresponding to each set of RSSI, the obtained μ and σ 2 are applied to the density function of the Gaussian distribution, as defned in equation (16).…”
Section: Experimental Environmentmentioning
confidence: 99%
“…Although technologies have seen continued advancement over recent decades, following the March 2011 accident at Japan's Fukushima Daiichi Nuclear Power Plant (FDNPP)notable advancements in the unmanned aerial vehicle (UAV) [9][10][11], unmanned ground vehicle (UGV) [12,13], and static/mobile distributed detection systems [14] were realized. Even years after this driver, progress continues across radiation detection, localization, and mapping, whether in underpinning detector materials research (e.g., novel plastics, high-dose semiconductors, dual gammaneutron scintillators) [15][16][17][18]; innovative, autonomous, and miniaturized deployment mechanisms [19][20][21]; or sensor-fusion/data visualization methodologies, progressing from 2D to 3D scenarios [22][23][24][25][26][27]. This research is not just occurring at a small number of institutions and laboratories, but it is a promising and increasingly cross-disciplinary area of active research around the world, applicable for nuclear plant decommissioning, nuclear security, and safeguards applications, whether or not in accident response [25].…”
Section: Radiation Detection Localisation and Mappingmentioning
confidence: 99%
“…The use of mobile systems should be mentioned as an alternative. Flanagan et al [ 16 ] propose the use of a mobile distributed sensor network using a public transportation system to protect large metropolitan areas from nuclear threats.…”
Section: Related Workmentioning
confidence: 99%